Personal Data Protection in the Era of Artificial Intelligence: A Legal Analysis of the Risks of Data Misuse - Melati Sukma; Hardin Hardin; Sutrisno Sutrisno (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed various sectors, including education, healthcare, finance, and public services. However, the extensive use of AI systems that rely on massive data collection and processing has raised serious concerns regarding the protection of personal data. This study aims to analyze the legal protection of personal data in the era of Artificial Intelligence and examine the risks of data misuse that may threaten individual privacy rights. The research employs a normative legal research method using statutory and conceptual approaches. Primary legal materials consist of Law Number 27 of 2022 concerning Personal Data Protection, while secondary materials include journals, books, and previous studies related to AI and data privacy. The findings indicate that AI technologies may lead to various forms of personal data misuse, such as unauthorized data collection, identity theft, algorithmic discrimination, data leakage, and profiling without user consent. Although Indonesia has established a legal framework for personal data protection, the implementation and supervision of such regulations remain inadequate due to limited public awareness, weak law enforcement, and rapid technological advancement. Therefore, stronger regulatory mechanisms, transparent data governance, and increased digital literacy are necessary to ensure that AI development remains aligned with human rights principles and privacy protection.